2020
DOI: 10.3389/fimmu.2020.00825
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of Endothelial Derived Exosomal HSPA12B in Regulating Macrophage Inflammatory Responses in Polymicrobial Sepsis

Abstract: Endothelial cell dysfunction contributes to sepsis induced initiate immune response and the infiltration of immune cells into organs, resulting in organ injury. Heat shock protein A12B (HSPA12B) is predominantly expressed in endothelial cells. The present study investigated whether endothelial HSPA12B could regulate macrophage proinflammatory response during sepsis. Wild type (WT) and endothelial cell-specific HSPA12B deficient (HSPA12B −/− ) mice were subjected to CLP sepsis. Mortality and cardiac function we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 50 publications
(74 reference statements)
1
31
0
Order By: Relevance
“…Heat shock protein A12B (HSPA12B) is mainly expressed in endothelial cells and transferred from released exosomes to macrophages ( Figure 5 ). By inhibiting the activation and nuclear translocation of NF-kB, it significantly increases the IL-10 level of LPS-stimulated macrophages and reduces the production of TNF-α and IL-1β ( Tu et al, 2020 ). In addition, HSPA12B reduces the expression of LPS-induced adhesion molecules and the production of pro-inflammatory cytokines via activating the PI3K/Akt signaling pathway of target cells ( Li et al, 2013 ), which contribute to reduce the migration and adhesion of macrophages to target cells in sepsis ( Tu et al, 2020 ).…”
Section: Effects Of Exosomes On Immune Cells In Sepsismentioning
confidence: 99%
See 2 more Smart Citations
“…Heat shock protein A12B (HSPA12B) is mainly expressed in endothelial cells and transferred from released exosomes to macrophages ( Figure 5 ). By inhibiting the activation and nuclear translocation of NF-kB, it significantly increases the IL-10 level of LPS-stimulated macrophages and reduces the production of TNF-α and IL-1β ( Tu et al, 2020 ). In addition, HSPA12B reduces the expression of LPS-induced adhesion molecules and the production of pro-inflammatory cytokines via activating the PI3K/Akt signaling pathway of target cells ( Li et al, 2013 ), which contribute to reduce the migration and adhesion of macrophages to target cells in sepsis ( Tu et al, 2020 ).…”
Section: Effects Of Exosomes On Immune Cells In Sepsismentioning
confidence: 99%
“…By inhibiting the activation and nuclear translocation of NF-kB, it significantly increases the IL-10 level of LPS-stimulated macrophages and reduces the production of TNF-α and IL-1β ( Tu et al, 2020 ). In addition, HSPA12B reduces the expression of LPS-induced adhesion molecules and the production of pro-inflammatory cytokines via activating the PI3K/Akt signaling pathway of target cells ( Li et al, 2013 ), which contribute to reduce the migration and adhesion of macrophages to target cells in sepsis ( Tu et al, 2020 ). Endothelial microparticles (EMP) has been shown to promote the maturation of plasma cell-derived dendritic cell (PDC) by up-regulating the expression of costimulatory molecules and promoting the release of IL-6 and IL-8 ( Angelot et al, 2009 ).…”
Section: Effects Of Exosomes On Immune Cells In Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…[178] Additionally, when heat shock protein A12B (HSPA12B), which is predominantly expressed in the endothelium and upregulates miR-126, was loaded into HU-VEC EVs via adenovirus-mediated overexpression, the EVs suppressed LPS-induced inflammatory cytokine secretion in murine macrophages via the downregulation of NF-B. [179] Finally, additional cell types have been investigated due to their established utility in biotechnological processes, increasing translational potential. Notably, Choi et al recently reported the development of human embryonic kidney 293T (HEK293T) EV-based delivery of super-repressor I(kappa)B (I B) to reduce sepsis-associated organ damage and mortality.…”
Section: Non-msc Evsmentioning
confidence: 99%
“…[ 178 ] Additionally, when heat shock protein A12B (HSPA12B), which is predominantly expressed in the endothelium and upregulates miR‐126, was loaded into HUVEC EVs via adenovirus‐mediated overexpression, the EVs suppressed LPS‐induced inflammatory cytokine secretion in murine macrophages via the downregulation of NF‐κB. [ 179 ]…”
Section: Preclinical Studies Of Evs As Sepsis Therapeuticsmentioning
confidence: 99%